2014
DOI: 10.1007/s10964-014-0194-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Associations Between Exposure to Sexy Online Self-Presentations and Adolescents’ Sexual Attitudes and Behavior

Abstract: Previous research suggests that adolescents' social network site use is related to their sexual development. However, the associations between adolescents' exposure to sexy self-presentations of others on social network sites and their sexual attitudes and experience have not yet been empirically supported. This study investigated reciprocal longitudinal relationships between adolescents' exposure to others' sexy self-presentations on social network sites and their sexual attitudes (i.e., sexual objectificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 51 publications
(113 reference statements)
4
32
0
Order By: Relevance
“…At the same time, previous research on the impact of SNSs on outcomes, such as sexual experience (van Oosten et al, 2015a) and appearance investment and body satisfaction (e.g., de Vries, Peter, de Graaf, & Nikken, 2016;de Vries, Peter, Nikken, & de Graaf, 2014), did not find any differences between adolescent boys and girls. To gain more insight into possible gender differences in the relationships between adolescents' gender role orientation and SNS use in general and sexy self-presentations in particular, we asked whether gender moderated the previously hypothesized reciprocal relationships (RQ1).…”
Section: Gender Differencesmentioning
confidence: 61%
See 2 more Smart Citations
“…At the same time, previous research on the impact of SNSs on outcomes, such as sexual experience (van Oosten et al, 2015a) and appearance investment and body satisfaction (e.g., de Vries, Peter, de Graaf, & Nikken, 2016;de Vries, Peter, Nikken, & de Graaf, 2014), did not find any differences between adolescent boys and girls. To gain more insight into possible gender differences in the relationships between adolescents' gender role orientation and SNS use in general and sexy self-presentations in particular, we asked whether gender moderated the previously hypothesized reciprocal relationships (RQ1).…”
Section: Gender Differencesmentioning
confidence: 61%
“…Moreover, one of the main functions of SNSs is to get in contact and interact with peers (Barker, 2009;Gross, 2004;Lenhart & Madden, 2007). One previous study found that stereotypical sexual attitudes predict adolescents' exposure to sexy self-presentations of others on SNSs (van Oosten et al, 2015a). Overall, then, the findings of previous studies suggest that hypergender orientation may form a predisposing factor of both adolescents' own engagement in sexy self-presentation and their exposure to others' sexy self-presentations.…”
Section: Predicting Adolescents' (Exposure To) Sexy Self-presentationmentioning
confidence: 87%
See 1 more Smart Citation
“…Recently, research has shown that adolescents also use social media to distribute sexually suggestive images of themselves. [2][3][4] For example, a content analysis revealed that one in five adolescents showed sexually revealing images on his or her online profile. 5 Another study demonstrated that up to half of the teenage profiles contain a sexy image of the adolescent user.…”
Section: Sexual Content Mass and Social Mediamentioning
confidence: 99%
“…There are a number of platforms that facilitate these interactions, including online dating sites (e.g., MyLOL.com; bebo.com), geosocial networking sites (e.g., Skout, Blendr, Grindr), sites where youth can engage in sex-based role playing, and apps for sharing sexually-explicit images online (e.g., Snapchat, sexting, emailing nude photos) (Gabarron, Serrano, Wynn, & Lau, 2014;Holloway, Dunlap, Del Pino, Hermanstyne, Pulsipher, & Landovitz, 2014;Jordán-Conde, Mennecke, & Townsend, 2014;van Oosten, Peter, & Boot, 2015). While many of these sites are relatively new and thus less is known about adolescent users, there is some preliminary evidence to suggest they are important points for future study.…”
Section: Sexual Content In Social Mediamentioning
confidence: 99%